Theoretical Mechanistic Studies of Rh‐Catalyzed C(sp3)—H Amination: A Comparison with Co Analogue and Metal Effects. Issue 12 (7th September 2020) - Yu, Yang; Luo, Gen; Yang, Jimin; Luo, Yi
Summary of main observation and conclusion: The mechanism of Rh‐catalyzed C(sp 3 )—H amination has been computationally investigated. The reaction mechanism mainly involves sequential C(sp 3 )—H activation, decarboxylation, nitrene migration insertion, and protonation steps. Competitive concerted metalation deprotonation (CMD) and external base assisted deprotonation (EBAD) pathways are found for the involved C(sp 3 )—H activation in both Rh and Co analogous systems. This is different from the previously reported C(sp 2 )—H activation, where the CMD is dominant. The key mechanistic difference between the two systems is found to be in the C(sp 3 )—H activation step. In comparison with Rh species, the lower activity of Co complex toward the C(sp 3 )—H activation could be ascribed to smaller atomic size of Co and thus larger steric repulsion between ancillary ligand and substrate along with the CMD pathway. In view of the EBAD pathway, however, the lower activity of Co species could be imputed to the triplet nature of Co center, which is against the electron transfer from the electron‐rich carbon atom of the deprotonating C(sp 3 )—H bond to the Co center. As to the subsequent decarboxylation and nitrene insertion steps, compared with the Co system, the relatively lower reactivity of Rh species is partially due to the stronger Rh—N bond, and the higher π(Rh—N) and π*(Rh—N) orbital energies of the corresponding transition state structure. Abstract : The Rh‐catalyzed C—H amination has been computationally investigated in comparison with Co analogous system, which involves sequential C(sp 3 )—H activation, decarboxylation, nitrene migration insertion, and protonation steps. Competitive concerted metalation deprotonation (CMD) and external base assisted deprotonation (EBAD) pathways are found for the C(sp 3 )—H activation in the both systems. The origin of the lower activity of the Co catalyst compared with Rh species toward the involved C(sp 3 )—H activation is distinct between the CMD and EBAD mechanisms.